Our mythical childhood ... : the classics and literature for children and young adults - Marciniak, Katarzyna, 1978- (Metaforms, 2016)
This volume offers a survey of the reception of Classical Antiquity in the literature for youngsters by applying regional perspectives from East-Central and Western Europe, Africa, Israel, Japan, New Zealand, Russia, and the United States. The title Our Mythical Childhood hints at the elusive and paradoxical potential of the ancient tradition that is both a fixed base shared by many people worldwide since their early life as well as a body of references constantly being reinterpreted in response to local challenges. The reader is given a deeper insight into the processes shaping children's and young adults' identities and their cultural formation. The volume fills an important gap in the scholarship and contributes to the development of Reception Studies in innovative and attractive directions.